Quality competition and pricing-to-market: A unified framework for the analysis of bilateral unit values - Ferrantino, Michael J.; Feinberg, Robert M.; Deason, Lauren (Wiley, 2012)
This article presents a unified framework for analyzing two factors that have been independently studied as determinants of unit values in international trade: product differentiation by quality (which suggests that unit values should be positively correlated with exporters' per capita income) and pricing‐to‐market (which suggests they should be positively correlated with importers' per capita income). No previous work has considered both exporter and importer income effects and allowed these effects to vary by product. On a large sample of bilateral unit values for 2005, we find that about 56% of all Harmonized System (HS)‐6 products demonstrate both significant exporter‐income effects and importer‐income effects, with the former predominating in prevalence and magnitude. Distance‐related effects appearing directly in prices appear significantly larger than one would expect as a result of shipping margins.